Growing Up in the Projects: The Economic Lives of a Cohort of Men Who Came of Age in Chicago Public Housing - Levitt, Steven D; Venkatesh, Sudhir Alladi (American Economic Review, 2001)
Growing Up in the Projects: The Economic Lives of a Cohort of Men Who Came of Age in Chicago Public Housing by Steven D. Levitt and Sudhir Alladi Venkatesh. Published in volume 91, issue 2, pages 79-84 of American Economic Review, May 2001